Ethical practice in internet research involving vulnerable people: lessons from a self-harm discussion forum study (SharpTalk). Issue 12 (24th September 2011) - Sharkey, Siobhan; Jones, Ray; Smithson, Janet; Hewis, Elaine; Emmens, Tobit; Ford, Tamsin; Owens, Christabel
Abstract : The internet is widely used for health information and support, often by vulnerable people. Internet-based research raises both familiar and new ethical problems for researchers and ethics committees. While guidelines for internet-based research are available, it is unclear to what extent ethics committees use these. Experience of gaining research ethics approval for a UK study (SharpTalk), involving internet-based discussion groups with young people who self-harm and health professionals is described. During ethical review, unsurprisingly, concerns were raised about the vulnerability of potential participants. These were dominated by the issue of anonymity, which also affected participant safety and consent. These ethical problems are discussed, and our solutions, which included: participant usernames specific to the study, a closed website, private messaging facilities, a direct contact email to researchers, information about forum rules displayed on the website, a 'report' button for participants, links to online support, and a discussion room for forum moderators. This experience with SharpTalk suggests that an approach to ethics, which recognises the relational aspects of research with vulnerable people, is particularly useful for internet-based health research. The solutions presented here can act as guidance for researchers developing proposals and for ethics committees reviewing them.